2020
DOI: 10.1111/plb.13202
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as a regulatory hub of plant hormone levels and action in stress situations

Abstract: Melatonin, a molecule first discovered in animal tissues, plays an important role in multiple physiological responses as a possible plant master regulator. It mediates responses to different types of stress, both biotic and abiotic. Melatonin reduces the negative effects associated with stressors, improving the plant response by increasing plant stress tolerance. When plants respond to stress situations, they use up a large amount of plant resources through a set of perfectly synchronized actions. Responses me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 142 publications
(97 citation statements)
references
References 116 publications
2
95
0
Order By: Relevance
“…Reports suggest that melatonin mediates several enzymes expression that detoxify excess H2O2 such as, CAT, glutathione/ascorbate reductases, peroxidases in addition to peroxiredoxins [17,79] and balances the ROS/RNS level through antioxidant action. Either endogenous or exogenous supplied melatonin induces its own synthesis presenting melatonin as specific regulator, an anti-stress manager and a plant master regulator [80,81]. Siddiqui et al [82] reported that melatonin induces photosynthetic enzymes, antioxidative system, proline metabolism and carbohydrate level under salt stress.…”
Section: Melatonin Decreases Heat Stress-induced Oxidative Stress By Enhancing the Antioxidative Machinery: The Effect Mediated By H2smentioning
confidence: 99%
“…Reports suggest that melatonin mediates several enzymes expression that detoxify excess H2O2 such as, CAT, glutathione/ascorbate reductases, peroxidases in addition to peroxiredoxins [17,79] and balances the ROS/RNS level through antioxidant action. Either endogenous or exogenous supplied melatonin induces its own synthesis presenting melatonin as specific regulator, an anti-stress manager and a plant master regulator [80,81]. Siddiqui et al [82] reported that melatonin induces photosynthetic enzymes, antioxidative system, proline metabolism and carbohydrate level under salt stress.…”
Section: Melatonin Decreases Heat Stress-induced Oxidative Stress By Enhancing the Antioxidative Machinery: The Effect Mediated By H2smentioning
confidence: 99%
“…It also plays a role in tissue growth and root generation, amongst others. 7,9,10,23,24 However, melatonin mainly induces the expression of RbOHs (respiratory burst oxidase homolog: plant NADPH-dependent oxidases), which generate superoxide anion, as well as the expression of superoxide dismutases (SOD), which leads to an increase in H 2 O 2 levels. 25 Melatonin induces the expression of several antioxidative enzymes such as catalases, peroxidases and peroxiredoxins, and also many elements of the ascorbate/glutathione cycle, with all them being involved in the control of excess ROS/RNS.…”
Section: Introductionmentioning
confidence: 99%
“…28 Generally, stressors induce an increase in endogenous melatonin levels in plants through the up-regulation of melatonin biosynthesis enzymes. 24 Lastly, the expression of a large number of enzymes related to plant hormone homeostasis is regulated by melatonin. The expression of genes that encode enzymes of the biosynthetic/catabolic pathways of plant hormones, such as indole-3-acetic acid (auxin), gibberellins, cytokinins, abscisic acid (ABA), ethylene, polyamines, salicylic acid, jasmonic acid (JA) and brassinosteroids, can be up-or down-regulated by melatonin in different situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin serves as a master regulator in plants due to its diversity of actions as a mediator between environmental factors, plant hormones and physiological responses. In this Special Issue, Arnao & Hern andez-Ruiz (2021) propose that melatonin acts as a regulatory hub of plant hormone levels and has an important role in stress situations. They outlined melatonin-mediated actions on phytohormones (auxins, GAs, CKs, ABA, ET, SA, JA, BR, PAs and strigolactones) in relation to its biosynthesis, catabolism, signalling elements and final responses.…”
mentioning
confidence: 99%